Factors Affecting Newborn Birth Weigth - Sri Winarsih; Esti Handayani; Ribkha Itha Idayanti; Munayarokh Munayarokh (Midwifery and Nursing Research, 2022)
Background: Fetal growth in the womb influenced by environmental conditions such as exposure to pesticides, exposure to cigarette smoke influenced by the pregnancy haemoglobin level and maternal age during pregnancy. During pregnancymaternal weight gain must be adequate, according to gestational age. Research objectives to know the factors affecting Newborn Birth weight Methods: Research design by cross sectional approach, for bivariate analysis using chi-square test on @ 5%, while for multivariate analysis using logistic regression Results: there is no correlation between exposure to cigarette smoke and birth weight ( p: 0.073.) There is relationship between the level of Haemoglobin and maternal age with the new born birth weight during pregnancy, weight gain during pregnancy with the baby's weight with a value of p